Purchase Decision: Do the Paylater Ease and Consumer Satisfaction Affect It? (Case Study on Shopee Paylater and Gojek Paylater) - Vietha Devia SS; Yulia Kusuma Wardani Putri (Faculty of Economics, Universitas Sriwijaya, 2022)
This study aims to examine whether the factors of consumer satisfaction and convenience of Paylater which are manifested in the variables of user age, payment tenor and interest rates can influence purchasing decisions. This study compares the use of Paylater on Shopee and Gojek. The consideration of comparing the two Paylater platforms is because these two platforms rank the most used by Paylater users in Indonesia. This study conducted in the city of Malang. This study uses primary data with a sample of respondents according to the Lemesshow formula. The number of sample used is 96 respondents for each object, namely Shope and Gojek. Then the primary data is processed using PLS. The results showed that user age, interest rates and consumer satisfaction had a significant effect on purchasing decisions at Shopee Paylater. While on Gojek Paylater, the variables that have a significant effect are interest rates and purchase satisfaction.